Efficacy and safety of indocyanine green tracer-guided lymph node dissection in minimally invasive radical gastrectomy for gastric cancer: A systematic review and meta-analysis - Zhao, Jixiang; Li, Ke; Wang, Zikang; Ke, Qingqing; Li, Jiapu; Zhang, Yizhen; Zhou, Xiaojiang; Zou, Yunzhi; Song, Conghua (Frontiers in Oncology, 2022)
Background: The implementation of indocyanine green (ICG) tracer-guided lymph node dissection is still in the preliminary stages of laparoscopic surgery, and its safety and efficacy for gastric cancer remain unclear. Methods: A systematic review was conducted in PubMed, Embase, Web of Science, the Cochrane Library, and Scopus to identify relevant subjects from inception to June 2022. The core indicators were the total number of harvested lymph nodes and the safety of the laparoscopic gastrectomy with ICG. Meta-analysis was performed to estimate the pooled weighted mean difference (WMD) and 95% confidence interval (CI). Results: Thirteen studies and 2027 participants were included (642 for the ICG-group and 1385 for the non-ICG group). The mean number of lymph nodes dissected in the ICG group was significantly more than that in the non-ICG group (WMD = 6.24, 95% CI: 4.26 to 8.22, P < 0.001). However, there was no significant difference in the mean number of positive lymph nodes dissected between the ICG and the non-ICG group (WMD = 0.18, 95% CI: -0.70 to 1.07, P = 0.879). In addition, ICG gastrectomy did not increase risk in terms of the operative time, estimated blood loss, and postoperative complications. Conclusion: ICG tracer with favorable safety increases the number of harvested lymph nodes but not the number of positive lymph nodes in laparoscopic gastrectomy. More high-quality, large sample size randomized controlled trials are still needed to enhance this evidence.